Contemporary Polling on Good as a Question on Man - Glinkowski, Witold (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Axiological topics, especially the concept of right and good and questions concerning nature of good, are intrinsic part of philosophy of men. This can be observed in contemporary philosophical tendencies, in particular those originated from philosophy of dialogue. In this perspective the emphasis in question of good moves from ontology to the philosophical anthropology. Good turns out to be interpersonal phenomenon, which is cohere with mutual dialogue and the drama of human existence, rather than with a „scene” understood as noumenal universe. Interesting notion of such philosophical approach to good can be found in thought of contemporary philosophers of dialogue and Józef Tischner's concept of philosophy of drama.